Analysis of the E-Performance System and Competence on Employee Performance with Work Motivation as a Mediator - Syafrinadina, Syafrinadina; Prawirosumarto, Suharno; Lusiana, Lusiana (Sistemasi: Jurnal Sistem Informasi, 2025)
This study aims to assess the impact of the e-performance system and human resource (HR) competencies on employee performance, with work motivation as an intervening variable at the Regional Secretariat Office of Indragiri Hilir Regency. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 3.0, data were collected through a questionnaire distributed to 177 respondents. The analysis revealed several key findings. First, the e-performance system positively and significantly influences work motivation. Similarly, HR competencies have a positive and significant effect on work motivation. Additionally, the e-performance system directly impacts employee performance in a positive and significant way. However, the relationship between HR competencies and employee performance was found to be positive but not significant. Work motivation, on the other hand, has a positive and significant influence on employee performance. Furthermore, work motivation mediates the relationship between the e-performance system and employee performance, as well as between HR competencies and employee performance, both with positive and significant effects. These findings highlight the critical role of motivation in enhancing employee performance through e-performance systems and HR competencies.